HUBUNGAN KEPADATAN VEKTOR DENGAN KEJADIAN DBD DI KELURAHAN BANDARHARJO KOTA SEMARANG - Astryana C. Lomi; Martini Martini; Ludfi Santoso (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Dengue Hemorrhagic Fever (DHF) is still a public health problem in Indonesia, especially in the city of Semarang. Bandarharjo is endemic regions and areas prone to tidal flooding or stagnant. The purpose of the study was to assess the relationship with the density of the vector of Dengue Fever cases in Bandarharjo Semarang. The design of this study using cross sectional method. The sample used in this study is a method of non-probability, purposive sampling. The research sample of 104 households, were observed 6-10 houses per RW. Measurement variables larvae density, pH, and salinity of the water using the observation sheet. Statistical analysis was performed with the chi-square test. The results showed that Bandarharjo Village is an area of high risk of dengue transmission with HI 47.11%, 16.15% CI, and BI 66.34. Total containers examined is 427 with 69 larvae positive containers. Containers which are most numerous larvae are bathtub located in the house. The statistical test showed there was no correlation between the density of larvae of dengue vectors with events (p = 0.5) in Bandarharjo. Suggested necessary monitoring activity mosquito nest eradication (PSN), as well as working with volunteers and mothers Family Welfare Guidance (PKK) for larval surveys once a week.